Ionic Hydrogen-Bonded Organic Frameworks with a Two-Photon Synergistic Color Change and Their Information Encryption Applications - Zhou, Bin; Cao, Li-Hui; Li, Bing-Sha; Chen, Xu-Yong; Bai, Xiang-Tian (ACS applied materials & interfaces, 2024)
Photochromic hydrogen-bonded organic frameworks (HOFs) can introduce different luminescent functional groups to achieve synergistic controlled multiple color change properties, which are in great demand for diverse information encryption applications. We report in this paper switchable photochromic and photoluminescent dual luminescent functional group HOFs constructed with synergistic effects by N,N′-bis(2-phenylalanine)-1,4,5,8-naphthalenediimine (H2PheNDI) and benzenecarboximidamide 4,4′-azobis(hydrochloride) (AZBH). The crystal powder of iHOF-41 is orange–red in color, which can be changed to black under the irradiation of a 365 nm ultraviolet (UV) light source for 15 min. The photoisomerization rate of the crystal solution under continuous UV irradiation for 5 h was close to 99%. The composite membranes can achieve the properties of photochromism and photoluminescence when they are discolored under 365 nm UV irradiation and, at the same time, excite red bright fluorescence. This work achieves the construction of HOFs based on switching biluminescent functional groups and explores the synergistic mechanism of the photoisomerization process and photochromism as well as its practical application in information encryption.